Chronic Pyruvate Supplementation Increases Exploratory Activity and Brain Energy Reserves in Young and Middle-Aged Mice - Koivisto, Hennariikka; Leinonen, Henri; Puurula, Mari; Hafez, Hani Sayed; Barrera, Glenda Alquicer; Stridh, Malin H.; Waagepetersen, Helle S.; Tiainen, Mika; Soininen, Pasi; Zilberter, Yuri; Tanila, Heikki (Frontiers in Aging Neuroscience, 2016)
Numerous studies have reported neuroprotective effects of pyruvate when given in systemic injections. Impaired glucose uptake and metabolism are found in Alzheimer's disease (AD) and in AD mouse models. We tested whether dietary pyruvate supplementation is able to provide added energy supply to brain and thereby attenuate aging- or AD-related cognitive impairment. Mice received ~ 800 mg/kg/day Na-pyruvate in their chow for 2- 6 months. In middle-aged wild-type mice and in 6.5-month-old APP/PS1 mice, pyruvate facilitated spatial learning and increased exploration of a novel odor. However, in passive avoidance task for fear memory, the treatment group was clearly impaired. Independent of age, long-term pyruvate increased explorative behavior, which likely explains the paradoxical impairment in passive avoidance. We also assessed pyruvate effects on body weight, muscle force and endurance, and found no effects. Metabolic post-mortem assays revealed increased energy compounds in nuclear magnetic resonance spectroscopy as well as increased brain glycogen storages in the pyruvate group. Pyruvate supplementation may counteract aging-related behavioral impairment but its beneficial effect seems related to increased explorative activity rather than direct memory enhancement.